Asuhan Keperawatan Jiwa pada Pasien dengan Risiko Perilaku Kekerasan di Wisma Cendrawasih RSJ Prof. Dr. HB Saanin Padang Tahun 2026 - Adila Salsa Bila; Vivi Yuderna; Dwi Happy Anggia Sari; Ramaita Ramaita (CV. ITTC INDONESIA, 2026)
The risk of violent behavior is a psychiatric nursing problem in patients with severe mental disorders due to the inability to control emotions and aggressive impulses that can harm themselves, others, and the environment. This study aims to implement psychiatric nursing care for patients at risk of violent behavior at Wisma Cendrawasih, Prof. Dr. HB Saanin Mental Hospital, Padang, in 2026. The research method used a descriptive case study with a nursing process approach through assessment, nursing diagnosis, intervention, implementation, and evaluation. Data collection was conducted through interviews, observation, and documentation on one patient. The assessment results indicated that the patient experienced emotional instability, irritability, aggressive behavior, and auditory hallucinations. Nursing interventions provided included deep breathing exercises and pillow hitting, adaptive verbal communication, medication education, and a spiritual approach. The results showed an increase in the patient's ability to control emotions, decreased aggressive behavior, and improved communication skills. It was concluded that comprehensive psychiatric nursing care was effective in helping reduce signs and symptoms of the risk of violent behavior and increasing the patient's self-control.